Diffraction and Vavilov-Cherenkov Radiation as a Novel Source of THz Radiation; RREPS-15. Radiation from Relativistic Electrons in Periodic Structures - Bleko V. V. Vitold Vladislavovich; Karataev P. V. Pavel Vladimirovich; Konkov (Kon'kov) A. S. Anatoliy Sergeevich; Kruchinin K. O. Konstantin Olegovich; Naumenko G. A. Gennadiy Andreevich; Potylitsyn A. P. Alexander Petrovich; Vaughan T. Thomas (Poster Session, 2015)
Title screen.